Taxonomic study of Central Asian species of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha: Cicadellidae: Macropsinae). II: Redescriptions of poorly known species, new synonyms, and description of a new willow-dwelling species - Tishechkin, Dmitri Yu. (Zootaxa, 2014)
Macropsis validiuscula Dubovsky, 1966, M. vicina (Horvath, 1897) = M. populicola Dubovsky, 1966 = M. albinata Dubovsky, 1966, syn. n. = M. albidula Dubovsky, 1966, syn. n., M. iliensis Mityaev, 1971 and M. elaeagnicola Dubovsky, 1966 are redescribed and illustrated based on material from Tien Shan Mts. (Kyrgyzstan) and Ferghana Valley (Uzbekistan), M. tienschanica Tishetshkin sp. n. from West Tien Shan Mts. (Kyrgyzstan) is described. M. iliensis Mityaev, 1971 is recorded from Kyrgyzstan for the first time. Data on host plants and male vibrational calling signals for all species considered are provided.